Analisis Dampak Penggunaan Gawai terhadap Perkembangan Belajar IPA Kelas V di SDS Mulya Asri Cikupa - Ferry Perdiansyah; Siti Hodijah (Journal on Education, 2023)
A gadget is a small machine or electronic device that is often used practically and has features that function to facilitate everyday human work. Gadgets have been widely used by all walks of life, including children. This creates positive and negative impacts in the use of gadgets. The problem discussed in this study is how the impact of using gadgets on the development of science learning for fifth grade students at SDS Mulya Asri Cikupa. Aims to describe or find out the impact of using gadgets in the development of science learning where in a lesson it involves the use of which results in the good or bad impact of gadgets on each material or science teaching material. This type of research is descriptive qualitative. The subjects of this study were teachers or homeroom teachers and fifth grade students. The data collection techniques used were observation, interviews, questionnaires and documentation. Data analysis using data reduction, data presentation and draw conclusions. Techniques for testing the validity of the data by extending observations, increasing persistence, triangulation, using reference materials, and member checks. The data found that 46.7% of students were in the very high category which stated that the impact of using gadgets that occurred in elementary schools had an influence on the development of science learning. Furthermore, the data obtained are 37.5% of students are in the high category, 10.3% of students are in the medium category, and 5.5% of students are in the low category which states that the impact of using gadgets that occur in schools has little effect on development. learn science.